Spin-Off and Profitability of Indonesian Islamic Banking - Dedik Fajar Nurkarim; Aulia Putri Wulandari; Zulfikar Bagus Pambuko (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The economic system could not be separated from the role of banking, either in funding, financing, or both. Today, Islamic bank was becoming an alternative banking service which had given new nuances to the business, both in terms of providing working capital or investment. This study aimed to investigate the effect of spin-off on Islamic Banks’ profitability with three control variables as market share, efficiency, and liquidity. This study used a quantitative approach from quarterly data from March 2013 to December 2019. The samples were two spin-off Islamic banks, namely Bank Aceh Syariah and Bank Tabungan Pensiunan Nasional Syariah. Based on the results of data analysis using the Ordinary Least Square technique, it was found that the spin-off, liquidity, and efficiency had significant impacts on the spin-off Islamic banks’ profitability. The market share has no significant effect on the profitability of Islamic banks